Evaluation of Low-Level Laser Therapy in TMD Patients - Simel Ayyildiz; Faruk Emir; Cem Sahin (Case Reports in Dentistry)
Light amplification by stimulated emission of radiation (laser) is one of the most recent treatment modalities in dentistry. Low-level laser therapy (LLLT) is suggested to have biostimulating and analgesic effects through direct irradiation without causing thermal response. There are few studies that have investigated the efficacy of laser therapy in temporomandibular disorders (TMD), especially in reduced mouth opening. The case report here evaluates performance of LLLT with a diode laser for temporomandibular clicking and postoperative findings were evaluated in two cases of TMD patients. First patient had a history of limited mouth opening and pain in temporomandibular joint (TMJ) region since nine months. Second patient’s main complaint was his restricted mouth opening, which was progressed in one year. LLLT was performed with a 685 nm red probed diode laser that has an energy density of 6.2 J/cm2, three times a week for one month, and application time was 30 seconds (685 nm, 25 mW, 30 s, 0.02 Hz, and 6.2 J/cm2) (BTL-2000, Portative Laser Therapy Device). The treatment protocol was decided according to the literature. One year later patients were evaluated and there were no changes. This application suggested that LLLT is an appropriate treatment for TMD related pain and limited mouth opening and should be considered as an alternative to other methods.